Sexual desire for non-normative sexual behaviors: differences between centennials and millennials considering sexual orientation - Alberto Paramio; Alberto Paramio; Ricardo Tejeiro; Antonio Romero-Moreno; Antonio Romero-Moreno; María Rusillo-Molina; Serafín Cruces-Montes; Serafín Cruces-Montes (Frontiers in Sociology)
IntroductionNon-normative sexual behaviors were traditionally studied from a psychopathological perspective, although nowadays a distinction is made between paraphilia (nonpathological) and paraphilic disorder (mental disorder).MethodsThe present study aims to examine the differences between a group of millennials (n = 173) and centennials (n = 159) in their appetite for these sexual behaviors without the preconception of these behaviors as harmful or pathological.ResultsDifferences in appetite related to exhibitionism and foot fetishism were found in the first instance, with millennials showing a greater appetite for these. When including sexual orientation in the analysis, in addition to exhibitionism and foot fetishism, differences were found in behaviors related to asphyxiation, bestiality and urophilia. Millennials and homobisexual centennials showed the highest appetite for exhibitionism behaviors, homo-bisexual centennials for choking behaviors and bestiality and homo-bisexual millennials for foot fetishism and urophilia-related behaviors.DiscussionExploring nonnormative behaviors from a non-psychopathological perspective will help us to understand the evolution of sexual appetite as part of human sexual diversity and to prevent risky behaviors.